Field data and prediction models of pesticide spray drift on coffee crop - Alves, Guilherme Sousa; Cunha, João Paulo Arantes Rodrigues da (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to generate drift curves from pesticide applications on coffee plants and to compare them with two European drift‑prediction models. The used methodology is based on the ISO 22866 standard. The experimental design was a randomized complete block with ten replicates in a 2x20 split‑plot arrangement. The evaluated factors were: two types of nozzles (hollow cone with and without air induction) and 20 parallel distances to the crop line outside of the target area, spaced at 2.5 m. Blotting papers were used as a target and placed in each of the evaluated distances. The spray solution was composed of water+rhodamine B fluorescent tracer at a concentration of 100 mg L‑1, for detection by fluorimetry. A spray volume of 400 L ha‑1 was applied using a hydropneumatic sprayer. The air‑induction nozzle reduces the drift up to 20 m from the treated area. The application with the hollow cone nozzle results in 6.68% maximum drift in the nearest collector of the treated area. The German and Dutch models overestimate the drift at distances closest to the crop, although the Dutch model more closely approximates the drift curves generated by both spray nozzles.